Modernisation de l’agriculture et santé mentale : les contradictions au travail - Philippe Spoljar (Perspectives Interdisciplinaires sur le Travail et la Santé)
Beyond the risk factors usually identified, the analysis of contexts of suicidal acts in agriculture requires taking into account a wide variety of involved registers (economic, social, technical, cultural, organizational, personal and family) and wonder about the dynamic processes that cross them. This article puts into perspective the convergence, at these different levels of determination, of the generic figure of « contradiction » , according to the different forms in which it can occur (double link, disqualification, cancellation, deculturation, downgrading, repression of emotions, casualization). This transverse glance helps to situate the process of embrittlement and dynamic critical that appear in contexts initially distant from the actual work and then come « attack links’ to crystallize in situations of impasse affecting professional practice hard family and personal life, and finally the farmers / breeders mental health.